2015
DOI: 10.1002/stem.2070
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Cardiac Disease Modeling Using Induced Pluripotent Stem Cells

Abstract: Genetic cardiac diseases are major causes of morbidity and mortality. Although animal models have been created to provide some useful insights into the pathogenesis of genetic cardiac diseases, the significant species differences and the lack of genetic information for complex genetic diseases markedly attenuate the application values of such data. Generation of induced pluripotent stem cells (iPSCs) from patient-specific specimens and subsequent derivation of cardiomyocytes offer novel avenues to study the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 106 publications
1
32
0
Order By: Relevance
“…2,23 Another focus of intensive research is the integration of these cells into preclinical drug safety assays, particularly to assess QT interval prolongation. 14,2429 While patch-clamp electrophysiology is the gold standard to assess electrical properties of hiPSC-CMs, it suffers from the major limitation of a very limited throughput, which is further restricted by the necessity to identify the CM subtype of interest based on AP morphology.…”
Section: Discussionmentioning
confidence: 99%
“…2,23 Another focus of intensive research is the integration of these cells into preclinical drug safety assays, particularly to assess QT interval prolongation. 14,2429 While patch-clamp electrophysiology is the gold standard to assess electrical properties of hiPSC-CMs, it suffers from the major limitation of a very limited throughput, which is further restricted by the necessity to identify the CM subtype of interest based on AP morphology.…”
Section: Discussionmentioning
confidence: 99%
“…hiPSC-CMs have been extensively used to recapitulate and study ex vivo cardiac disorders associated with conduction defects or electrocardiogram (ECG) abnormalities such as long QT syndrome (Reviewed in [116]). Importantly, these studies have demonstrated a strong correlation between results obtained with hiPSC-CMs and primary adult human CMs.…”
Section: Modeling Dilated Cardiomyopathy: Dmd Case Studymentioning
confidence: 99%
“…Human pluripotent stem cell (hPSC) derived cardiomyocytes (CM) represent a promising and powerful tool for anti-arrhythmic drug (AAD) screening, and have been exploited to model a growing number of arrhythmogenic cardiac electrical disorders at a single cell level 9 . Investigations have predominantly focused on diseases of the ventricles, in some part because current differentiation protocols produce predominantly ventricular-like CMs, with a small minority of atrial-like and nodal-like cells 10 .…”
Section: Introductionmentioning
confidence: 99%